Characterization of out-of-plane tensile stress–strain behavior for GFRP composite materials at elevated temperatures. (15th June 2022) - Hao, Ziqing; Chen, Guangchang; Ke, Hongjun; Deng, Linlin; Liu, Liu
Abstract: Three-dimensional stress–strain constitutive parameters in various environments are essential for understanding the mechanical behavior of thick cross-section composite load-bearing structures. This work aims to expand a short-beam bending test combined with a digital image correlation method to obtain the out-of-plane (interlaminar) stress–strain behavior for polymer–matrix composites at elevated temperatures. A simple and repeatable digital speckle pattern fabrication method was used based on the water transfer printing (WTP) technique to reduce deformation measurement uncertainty induced by the quality of the speckle pattern. The effects of DIC parameters and misalignment of the DIC stereo camera system on the uncertainty of deformation measurement have been studied. The out-of-plane properties, including elastic modulus and tensile strength for a 50-ply thick S6C10/AC318 glass/epoxy unidirectional panel, have been obtained at elevated temperatures for the first time. The experimental results showed that the out-of-plane modulus and tensile strength were 15.95 GPa and 76 MPa at room temperature. The modulus was nearly unchanged at 50 °C and decreased 18% at 80 °C. The out-of-plane tensile strength decreased 9% at 50 °C and 22% at 80 °C, respectively, indicating that the tensile strength degradation is more sensitive to temperature rising than the modulus. The study suggests that the improved short-beam bending test combined with the DIC method can guarantee reproducible results and usability at elevated temperatures. Highlights: The transverse modulus and tensile strength were measured at elevated temperatures The modulus decreased 18%, while the tensile strength decreased 22% at 80 °C The transverse tensile strength is more sensitive to temperature than the modulus. The short-beam test can guarantee reproducible results at elevated temperatures